2017
DOI: 10.1113/ep086639
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related microvascular dysfunction: novel insight from near‐infrared spectroscopy

Abstract: What is the central question of this study? Can near-infrared spectroscopy (NIRS)-derived post-occlusion tissue oxygen saturation recovery kinetics be used to study age-related impairments in microvascular function? What is the main finding and its importance? Using a previously established 5 min cuff occlusion protocol, we found that NIRS-derived indices of microvascular function were markedly reduced in elderly compared with young participants. However, when we controlled for the absolute level of vasodilato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 52 publications
(101 reference statements)
3
65
1
Order By: Relevance
“…Measurement of the sensitivity of STO 2 upslope has been well documented and supported in recent years, because NIRS is a low‐cost, easy‐to‐use methodology and has low test–retest variability both within and between days (McLay et al., ; Rosenberry et al., ; Soares et al., ). Soares et al () found that STO 2 upslope was positively correlated with %FMD of the brachial artery, a measure of cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Measurement of the sensitivity of STO 2 upslope has been well documented and supported in recent years, because NIRS is a low‐cost, easy‐to‐use methodology and has low test–retest variability both within and between days (McLay et al., ; Rosenberry et al., ; Soares et al., ). Soares et al () found that STO 2 upslope was positively correlated with %FMD of the brachial artery, a measure of cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research by Rosenberry et al. () indicated that the STO 2 upslope is likely to be influenced by the magnitude of the stimulus (i.e. the amount of ischaemia associated with cuff occlusion) as measured by the minimal STO 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, properly assessing vascular function within conduit artery and the microvascular circulation is important for prevention, early detection, and monitoring of CVD . In relation to this, the use of near‐infrared spectroscopy (NIRS) combined with vascular occlusion test (VOT) technique (NIRS‐VOT) has been demonstrated to be a useful tool for assessment of microvascular function . This technique evaluates microvascular reactivity by assessing the steepness of the upslope of the muscle oxygen saturation signal (reperfusion slope, % per s), typically following a 5‐min period of limb occlusion .…”
Section: Introductionmentioning
confidence: 99%